Peran Mahasiswa dalam Meningkatkan Kesadaran Kesehatan Masyarakat Desa Reroroja melalui Edukasi dan Kerja Bakti - Diana, Maria; Rehing, Emilia Yunritati (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2025)
Public awareness of the importance of environmental health, particularly in waste management, remains very low, which can lead to various diseases and an uncomfortable living environment. This community service activity aimed to increase awareness and participation among residents of Reroroja Village, Magepanda District, Sikka Regency, through educational activities on health and collective community clean-up activities involving students. The method used was descriptive qualitative research, with data collected through direct observation, semi-structured interviews, and participation in community clean-up activities. The results showed that student involvement in both educational efforts and practical actions improved community understanding of the importance of Clean and Healthy Living Behavior (PHBS), especially in waste management and the prevention of environment-related diseases. Active community participation also strengthened the values of mutual assistance and togetherness, while creating opportunities for long-term collaboration between educational institutions and the community. These findings indicate that participatory approaches combining education and practical actions are highly effective in increasing environmental awareness and encouraging cleaner, healthier, and more sustainable lifestyles.